Enhance Security Issues Using Data Cipher Algorithm in Cloud - Singh, Jaswinder; Rana, Runa (International Journal of Computer Sciences and Engineering, 2014)
Cloud Computing is a internet based computing that facilities hardware, network and software resources and provide flexible infrastructure on demand as pay per usage. The benefits of cloud computing is due to its reduced cost, resource sharing and performance. Cloud is based on the difficulty of securing storage data and maintain privacy. The security is the only problem in the cloud .Security is not provided in the cloud ,many companies have their own unique security structure Though , Amazon has its own security structures. The data placed in the cloud is accessible to everyone . To overcome this difficulty ,we have proposed RSA algorithm between cloud service provider and the user. The aim of our proposed work is to enhance security issues and maintain privacy.